Drug Delivery Systems and Flavonoids: Current Knowledge in Melanoma Treatment and Future Perspectives - Cunha, Catarina (2022)
Melanoma is an aggressive form of skin cancer with a high prevalence in the population. An early diagnosis is crucial to cure this disease. Still, when this is not possible, combining potent pharmacological agents and effective drug delivery systems is essential to achieve optimal treatment and improve patients' quality of life. Nanotechnology application in biomedical sciences to encapsulate anticancer drugs, including flavonoids, in order to enhance therapeutic efficacy has attracted particular interest. Flavonoids have shown effectiveness against various types of cancers including in melanoma, but they show low aqueous solubility, low stability and very poor oral bioavailability. The utilization of novel drug delivery systems could increase flavonoid bioavailability, thereby potentiating its antitumor effects in melanoma. This review summarizes the potential of different flavonoids in melanoma treatment and the several nanosystems used to improve their biological activity, considering published information that reported improved biological and pharmacological properties of encapsulated flavonoids.